INTERNALISASI NILAI-NILAI ISLAM DALAM PRAKSIS DEMOKRASI DI INDONESIA - Adi Nur Rohman (Universitas Nasional, 2018)
Democracy is seen as an ideal paradigm to achieve peace and justice in a particular country. BeingMuslim-populated country, Indonesia encounters a dilemma where democracy draws pros and conseven within Islamic point of view. This paper is to decipher democracy in Islam and elaborateIslamic values in the practice of democracy in Indonesia. This is a literary study focusing on Islamand democracy in Indonesia. The conclusion is that the Western democracy does not fit in withIndonesia whose people believe in one god. However, democracy is essentially part of Islam, whichis a set of values. In practice, it seems that internalization of Islamic values into practice ofdemocracy in Indonesia is inevitable, because democracy in Indonesia is in accordance with Islam.Keywords: Islamic-values, democracy, Indonesia, Islam, muslim